The Motivation of Technological Scenarios in Augmented Reality (AR): Results of Different Experiments - Cabero-Almenara, Julio; Roig-Vila, Rosabel (Applied sciences, 2019)
Augmented Reality (AR) is an emergent technology that is acquiring more and more relevance in teaching every day. Together with mobile technology, this combination arises as one of the most effective binomials to support significant and ubiquitous learning. Nevertheless, this binomial can only prove valid if the student is motivated to use it during the learning process. An attempt was made through the implementation of Keller’s Instructional Material Motivational Survey model o determine the degree of motivation of Pedagogy, Medicine and Art students from the University of Seville for using AR-enriched notes available by means of mobile devices in the classroom. Three applications designed for the subjects of Educational Technology, Anatomy and Art served to assess it positively in terms of the motivation raised by the participation in the experiment, as well as regarding academic performance improvement. It can additionally be stated that our main finding was a link between students’ motivation to use the enriched notes and the performance obtained in the subject in which they use them. Evidence was also found that the utilization of Augmented Reality benefits the learning process.